2016
DOI: 10.1186/s12872-016-0358-4
|View full text |Cite
|
Sign up to set email alerts
|

The interaction effects of risk factors for hypertension in adults: a cross-sectional survey in Guilin, China

Abstract: BackgroundThe prevalence of hypertension in adults is increasing each year and has become a main public health issue worldwide. We must consider the impact of both individual factors and interactions among these factors on hypertension in adults. This study was designed to elucidate the clinical and metabolic characteristics of the prevalence of hypertension in adults and to explore the risk factors and interactions among these factors in adults with hypertension.MethodsWe used overall random sampling to condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Such disagreement may be due to the study's self-report questionnaire design and the fact that women are generally more likely to say they are unwell than men. In addition, results of the present work coincide with Yu et al [19] crosssectional study of 6660 people undergoing a health check in China from July to November 2012, logistic regression analyses found that advanced age and high BMI were significant risk factors for hypertension and had a positive association impact of the prevalence of hypertension in adults. This finding also agrees with the study by ElShazly and Hegazy [20] finding that age, sex, family size, socioeconomic score and occupation were the main determinants of hypertension.…”
Section: Discussionsupporting
confidence: 89%
“…Such disagreement may be due to the study's self-report questionnaire design and the fact that women are generally more likely to say they are unwell than men. In addition, results of the present work coincide with Yu et al [19] crosssectional study of 6660 people undergoing a health check in China from July to November 2012, logistic regression analyses found that advanced age and high BMI were significant risk factors for hypertension and had a positive association impact of the prevalence of hypertension in adults. This finding also agrees with the study by ElShazly and Hegazy [20] finding that age, sex, family size, socioeconomic score and occupation were the main determinants of hypertension.…”
Section: Discussionsupporting
confidence: 89%
“…Statistical analysis would be of assistance in this study; however, analyses are highly intractable for precise study because plasma BNP levels are associated with many confounding factors, including ageing, gender distinction, body mass index (BMI), LV dysfunction, and renal dysfunction 23,24 . Additionally, serum UA is associated with the same factors 14,25 . To explore the precise effects of high UA on plasma BNP and the observed LV dysfunction, advanced statistical procedures are warranted.…”
Section: Introductionmentioning
confidence: 90%
“…Hypertension (HTN), one of the most well-known chronic diseases, has a multifactorial nature linked to the possible interaction of genetic and environmental risk factors [1,2]. Furthermore, HTN is a very important modifiable risk factor for cardiovascular morbidity and mortality [3,4].…”
Section: Introductionmentioning
confidence: 99%